Biologic therapy is associated with a mild decrease in the rate of hospitalizations in pediatric IBD - Gil Berkovitch; Shlomi Cohen; Ronit Lubetzky; Dana Singer; Anat Yerushalmy-Feler (BMC, 2021)
Abstract Background The effect of biologic therapy on the incidence of inflammatory bowel disease (IBD)-related hospitalizations is controversial. The high efficacy of biologic agents is weighted against potential therapy-related adverse events, however, there are no data on the effect of biologic therapy on the indications for hospitalization in IBD. We aimed to evaluate the impact of biologic therapy on the indications and rate of hospitalization in pediatric IBD. Methods This retrospective cohort study included all children (< 18 years of age) with IBD who were hospitalized in our medical center from January 2004 to December 2019. Data on demographics, disease characteristics and course, and therapy were collected, as were the indications for and course of hospitalizations. We evaluated the relationship between therapy with biologic agents, indications and rates of hospitalization. Results Included were 218 hospitalizations of 100 children, of whom 65 (65%) had Crohn's disease and 35 (35%) had ulcerative colitis. The indications for hospitalization were IBD exacerbations or complications in 194 (89%) and therapy-related adverse events in 24 (11%). The patients of 56 (25.7%) hospitalizations were receiving biologic therapy. In a multivariate analysis, no correlation between therapy and indication for hospitalization was found (p = 0.829). Among children under biologic therapy, a decrease in the rate of hospitalizations from 1.09 (0.11-3.33) to 0.27 (0-0.47) per year was observed for patients that were hospitalized during 2016-2019 (p = 0.043). Conclusion Biologic therapy did not influence the indication for hospitalization, but were associated with a decrease in the rate of hospitalization during 2016-2019 in pediatric IBD.